Analisis Faktor Keamanan Dan Probabilitas Kelongsoran Lereng Di Jalan Batu Besaung Kelurahan Sempaja Utara Kecamatan Samarinda Utara Kota Samarinda Provinsi Kalimantan Timur - Enggar Salsabilla Pramesty; Revia Okatviani; Albertus Juvensius Pontus (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
A slope is an area of ​​morphology that has a certain geometry, namely the highest and lowest parts and has the potential for landslides if it is in an unstable condition (Wesley & Pranyoto, 2010 in Khodijah, et al, 2022). A slope can be composed of soil, rock, or both. Slope stability is influenced by slope geometry, physical and mechanical characteristics of the slope-forming material, water (hydrology and hydrogeology), rock weak plane structure (location, direction, frequency, mechanical characteristics), natural stresses in the rock mass, local stress concentrations, vibrations ( natural: earthquakes; and human actions: effects of blasting, effects of heavy equipment passing by), climate, the results of mine workers' actions, and thermic effects (Moshab, 1997 in Arif, 2016).